Lockdown- of the people, for the people and by the people - Jampani, Ravitheja; Nayanatara, Vasireddy (International Journal Of Community Medicine And Public Health, 2020)
COVID-19 pandemic affected almost all countries in world (except North Korea). Pandemic originated in Wuhan and spread its wings across the world. Many countries started taking war foot measures to control spread of pandemic, isolate its patients and impose lockdown over its population. People from various countries understood and the governments made people understand the effects of pandemic COVID-19. Lock down was implemented several times in history of mankind. The Plague pandemic, Cholera, Influenza pandemic of 1918 and SARS 2002 pandemic are known situations where lockdown was implemented to contain the damage caused. COVID-19 is probably the first time in history of mankind where lockdown was implemented in most of the world countries at same time in a never before seen magnitude. Number of countries under lockdown, number of days of lockdown and number of deaths caused by COVID-19 are never seen in history.